Nursing personnel training: a pilot study on attitude change, through a workshop on ethics and humanities - Guillermo Cantú-Quintanilla; Nuria Aguiñaga-Chiñas; Anneke Farías-Yapur (Revista de Estudios e Investigación en Psicología y Educación, 2021)
Nursing has emerged as one of the main professions with a humanistic sense specialized in health care. The accent on personal development favored by training in humanities allows for questioning whether a training specifically focused on the workplace abilities enhances personal fulfilment at work. A pilot workshop on Ethics and Humanities at Work was offered in tertiary hospital to assess the influence of ethics and humanities in attitude toward work. Nineteen nurses completed the workshop; attitude towards change and attitude towards teamwork increased significantly. In this pilot study we found that the workshop influenced attitude towards change at work and teamwork. Since an attitude is made up of the cognitive, affective, and behavioral components, the change in one of these has the capacity to modify part of the others.